Towards Ultrasound-guided Spinal Fusion Surgery - Manbachi, Amir (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This thesis describes the design and fabrication of ultrasound probes for pedicle screw guidance. The author details the fabrication of a 2MHz radial array for a pedicle screw insertion eliminating the need for manual rotation of the transducer. He includes radial images obtained from successive groupings of array elements in various fluids. He also examines the manner in which it can affect ultrasound propagation. Nominated as an outstanding Ph.D. thesis by the University of Toronto, Ontario, Canada Describes the design and fabrication of 2Mhz ultrasound probes for pedicle screw guidance Explores radial array designs that eliminate the need for manual rotation of the transducer Depicts a quantitative method for investigating the directionality distribution for analysis of ultrasound propagation with potential uses for a variety of applications.